SIKAP, POLA KONSUMSI, DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI KONSUMEN RESTAURANT CEPAT SAJI (FAST FOOD) DI BANDAR LAMPUNG - Dinda Anisa Yuliana; Rabiatul Adawiyah; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
Thisl studyl aimsl tol analyzel thel attitude ofllconsumers, foodl consumption pattern, andl factors affecting thel consumption at fast foodl restaurant inl Bandar Lampungl City. Thisl research wasl conducted atlinternational franchised fast food restaurants inl Bandar Lampungl City. Thel research methodl is al survey withl the accidentall sampling ltechnique. Thel number ofl samples inl this researchl were 70 consumers whol had bought or consumed at international franchised fast food restaurants atl least oncel in thel last onel month. Thel research datal were analyzedl by usingl fishbein lmulti-atribute lanalysis, descriptivel statistics analysis, andl multiple linear regressionl analysis. Datal collection wasl conducted from lJune-Julyl 2022. Thel results showedl that thel consumers who boughtl or consumed atlinternational franchised fast food restaurants is because of its taste, hygiene, and services. Consumers more likely to buy at a international franchised fast food restaurants that served fried chicken as it main course like McD and KFC. The average amount of purchased were two menus per transaction and average amount of frequency were three times per month with reason of purchased were great taste, easy to find, and practical. Factors that affected the consumption were incomes, international franchised fast food restaurant’s prices, and consumers habitual variables.